Mixed Questions and the Scope of Federal Habeas Review: Consideration of Miranda Claims in Thompson v. Keohane - Meyers, Rachel (1997)
Federal habeas corpus review has a long historical tradition, at common law and in the United States. Over time, federal habeas review has expanded to its modern dimensions, which permit lower federal courts to overturn decisions of the states' highest courts. When federal courts review claims raised by state prisoners, the mandate to protect individual constitutional rights competes with other fundamental constitutional values: the promotion of federalism, in the form of respect for state court judgments, finality and fairness. This Comment analyzes a federal habeas claim of a Miranda violation, a claim which has traditionally been deemed a mixed question of law and fact and therefore subject to de novo review by the lower federal courts. Using the Thompson case as both an example and a point of reference, this Comment discusses the need for reforms to the federal habeas system and the limited impact of the largely procedural reforms implemented in the Antiterrorism and Effective Death Penalty Act of 1996